EFEKTIFITAS SENAM YOGA DAN SENAM LANSIA TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI DI POSYANDU LANSIA KELURAHAN WIRONANGGAN - Ahmad Syamsul Bahri (STIKES Estu Utomo, 2024)
Background : Hypertension is the most common disease experienced by the elderly in Indonesia. Hypertension in the Wironanggan village area is the highest cause of death in the elderly. In Wironanggan village there are 1.531 elderly and 293 elderly who have hypertension. Yoga and exercise for the elderly is an alternative non-pharmacological treatment of hypertension. Yoga exercise can stimulate the release of endorphine hormones. Endorphins are neuropeptides that the body produces when relaxed or calm. Elderly exercise can be used as an alternative to non-pharmacological hypertension treatment because elderly exercise can relax blood vessels. Objective : the purpose of this study was to determine the effectiveness of yoga and exercise for the elderly on reducing blood pressure in the elderly with hypertension at the posyandu for the elderly Wironanggan village Methods : quasy experimental research design pre test - post test design with a sample of 30 respondents taken by accidental random sampling method. Tre research instrument used a checklist and obsevation sheet. Data analysis using a non-parametric test, namely the wilcoxon test Research Results : wilcoxon test result pre and post giving yoga and gymnastics for the elderly for systolic blood pressure obtained a p value of 0,000 and the result of the wilcoxon test pre and post giving yogs and exercise for the elderly diastolic blood presure obtained a p value of 0,000. bith test result showing p <0,05 means that there is a significant or significant difference in giving yoga and elderly exercise to lowering blood pressure. From these data, it can be concluded that there is an effect of yoga and elderly exercise in the elderly with hypertension Conclusion : there is a effectiveness of yoga and ecercise for the elderly to reduce high blood pressure in the elderly with hypertension at the posyandu for the elderly Wironanggan Village